PERAN KOMUNITAS JELAJAH DALAM MENGEMBANGKAN SEKTOR PARIWISATA DI KOTA SAMARINDA - Andi Hafitz Khanz; Enos Paselle; Heryono Susilo Utomo (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
This study aims to determine the role played by Jelajah Community to develop the tourism sector in Samarinda City as agents of change and social control. The role of the Jelajah Community is focused on activities and activities which is carried out through research focus, namely: (1) Exploring a destination tourism which is easily accessible or not, (2) Carrying out socialization activities and promotion to the public through social media, (3) Becoming a medium and evaluator for Stackholder in this case the Department of Tourism, both East Kalimantan Province and City of Samarinda (4) Inhibiting factors in implementing the role of youth in sector development tourism. The result of this research is shows the role of Jelajah Community in developing the tourism sector in Samarinda City shows that role has been going well, this is due to Jelajah Community can be able to bridge various actors both government and society in his efforts to develop the tourism sector in Samarinda City, this has been proven with the fact that the information dissemination shared by Jelajah Community is very spread quickly, and several times the documentation of the results of activities carried out viral. The impact of which the destination is visited by many tourists and gets attention from the government.Keyword : Jelajah Community, Role, Tourism, Youth